PENGARUH KEBIJAKAN HARGA ECERAN TERTINGGI MINYAK GORENG TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Septian, Esa; Wulandari, Septi (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
Fluctuations in cooking oil prices due to policy changes have triggered consumer unrest and prompted the government to set a Highest Retail Price (HET) to maintain people's purchasing power. This study aims to analyze the effect of the HET policy on consumer purchasing decisions in Tepas Village, Ngawi Regency. Using a quantitative explanatory approach with a causal-comparative survey design, data were collected through questionnaires to 40 respondents selected using the Accidental Sampling technique. Measurements used a 5-point Likert scale and were analyzed through descriptive tests, normality, Pearson correlation, simple linear regression, and one-sample t-tests using JASP. The results showed that HET had a very strong and significant effect on purchasing decisions (r = 0.950; p < 0.001; R² = 0.902). Consumers tend to continue buying cooking oil when they feel the price is stable, certain, and affordable. These findings support the theory of consumer behavior and strengthen previous research related to staple food price policies. This study has limitations in terms of coverage and number of respondents. Further research suggests expanding the location, increasing the number of samples, and using a mixed approach to explore the psychological and socio-cultural factors that influence purchasing decisions.